2006
DOI: 10.1590/s0001-37652006000100008
|View full text |Cite
|
Sign up to set email alerts
|

Differentially displayed expressed sequence tags in Melipona scutellaris (Hymenoptera, Apidae, Meliponini) development

Abstract: We have compared gene expression, using the Differential Display Reverse Transcriptase -Polymerase Chain Reaction (DDRT-PCR) technique, by means of mRNA profile in Melipona scutellaris during ontogenetic postembryonic development, in adult worker, and in both Natural and Juvenile Hormone III-induced adult queen. Six, out of the nine ESTs described here, presented differentially expressed in the phases L1 or L2, or even in both of them, suggesting that key mechanisms to the development of Melipona scutellaris a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…DD-PCR technique is considered a powerful genetic screening tool for complicated dynamic tissue processes, particularly when multiple, limited-sized samples are involved, because it allows for simultaneous amplification of multiple arbitrary transcripts [ 15 ]. This technique has been developed as a tool to detect and compare altered gene expression in eukaryotic cells [ 16 ], to screen mRNAs, and to characterize differentially expressed mRNAs [ 17 - 20 ]. Many publications described the enhancement of the insect immune system and induction of AMPs due to stress and/or bacterial challenge [ 8 - 10 , 12 , 13 , 21 - 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…DD-PCR technique is considered a powerful genetic screening tool for complicated dynamic tissue processes, particularly when multiple, limited-sized samples are involved, because it allows for simultaneous amplification of multiple arbitrary transcripts [ 15 ]. This technique has been developed as a tool to detect and compare altered gene expression in eukaryotic cells [ 16 ], to screen mRNAs, and to characterize differentially expressed mRNAs [ 17 - 20 ]. Many publications described the enhancement of the insect immune system and induction of AMPs due to stress and/or bacterial challenge [ 8 - 10 , 12 , 13 , 21 - 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, many bands were induced as a result of bacterial-challenge at different time intervals post-infection. DD-PCR technique is considered a powerful genetic screening tool for complicated dynamic tissue processes, to detect and compare altered gene expression in eukaryotic cells, and to screen and to characterize differentially expressed mRNAs (Santana et al, 2006), because it allows for simultaneous amplification of multiple arbitrary transcripts. Many publications described the enhancement of the insect immune system and induction of AMPs due to stress and/ or infection (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, others reported that DD-PCR is a powerful tool for the characterization of altered gene expression in eukaryotic cells (Mong et al, 2002). DD-PCR has been recommended for the isolation of mRNAs of oncogenes (Gonsky et al, 1997), novel genes expressed in human lung and wound healing (Lurton et al, 1999;Soo et al, 2002) and key genes involved in development of Melipona scutellaris (Santana et al, 2006). Sturtevant (2000) reviewed many applications of DD-PCR in medical mycology.…”
Section: Discussionmentioning
confidence: 99%